Effect of Resistance Training and Diet Intake on Spleen Structure of Ovariectomized Wistar Rats - Santana, Erika Steffany dos Santos; de Oliveira, Carolinne Alves; Lima, Francisca Iranni Alves; Nucci, Ricardo Aparecido Baptista; Fonseca, Fernando Luiz Affonso; Maifrino, Laura Beatriz Mesiano (Journal of Health and Allied Sciences NU, 2021)
Introduction Exercise is a key factor in immunity which may be affected by a different diet intake. Thus, we aimed to analyze the effects of diet intake and resistance training on spleen structure of ovariectomized female animals.Materials and Methods Female Wistar rats were divided into eight experimental groups: sedentary and nonovariectomized animals plus vegetable protein diet (CVS) or animal protein diet (CAS); trained and nonovariectomized rats plus vegetable protein diet (CVT) or animal protein diet (CT); sedentary and ovariectomized groups plus vegetable protein diet (VOS) or animal protein diet (AOS); and trained and ovariectomized animals plus vegetable protein diet (VOT) or animal protein diet (AOT).Results Groups submitted to both animal protein diet and resistance training, mainly ovariectomized groups, presented a great variability of collagen fibers type III, white pulp, and follicle structure in relation to the other spleen constituents.Conclusion Resistance training with a vegetable protein diet may play a key factor to maintain spleen’s immune responses across age. However, animal protein diet is suggested to decrease spleen’s immune activity.
Keywords: aging; diet; exercise